Application of quality function deployment technique for searching of device characteristic and design of health care monitoring device - Meemongkol, Napisporn; Junsong, Peerayu; Santiamorntut, Wannarat (Asia-Pacific Journal of Science and Technology, 2017)
This research introduces an application of Quality Function Deployment (QFD) for health care monitoring device. First of all the objectives of this research is to design and building of health care monitoring device for application using in critical patients correlate to responsive of staff requirement. Second, the staff requirement data analysis will be analyzed for useful as device improvement in the future. The destination of this research is to design shape and usability the device accord to user requirement. Methodology began by conducting a survey the critical patient data of Songklanagarind hospital, which led to data for the specification of the sample group. In the secondary process, the collection of user requirement and design questionnaires to the calculation of importance score for each user requirement. The user requirement and importance score will be input data for QFD technique. The analysis of QFD technique divided into 2 matrixes is product planning matrix that translate user requirement into technical requirement, and parts deployment matrix that translate technical requirement into parts characteristic.The results of this research found that consequence from QFD technique, the shape and usability of device can reveal that the response to user requirement.